Identification of key modules and genes in response to high-temperature stress in Platostoma palustre based on WGCNA - Xiufang Li; Fan Wei; Changqian Quan; Meihua Xu; Danfeng Tang (BMC Plant Biology)
Abstract Platostoma palustre (Blume) A. J. Paton is one of the important medicinal and edible plants in China, and it is widely cultivated in tropical and subtropical regions of southern China. In these areas, high-temperature stress (HTS) is often one of the unfavorable environmental factors affecting the growth and yield of P. palustre. Nevertheless, the molecular mechanism underlying the response of P. palustre to HTS remains unclear. In this study, we used two varieties of P. palustre, LSL and MDG, as experimental materials to identify key genes involved in the response of P. palustre to HTS by employing transcriptome sequencing technology, thereby revealing the molecular mechanism underlying its adaptation to HTS. The results showed that HTS significantly influenced the plant height, above-ground fresh weight, root fresh weight, root growth, chlorophyll a, chlorophyll b, chlorophyll a + b, and carotenoid content of P. palustre plants. MDG exhibited stronger high-temperature tolerance compared to LSL. Under HTS, 8352 DEGs were up-regulated and 9201 DEGs were down-regulated in HT_LSL_vs_CK_LSL, while 5433 DEGs were up-regulated and 6325 DEGs were down-regulated in HT_MDG_vs_CK_MDG, suggesting a significant difference in gene expression levels between LSL and MDG under HTS. KEGG enrichment analysis showed the pathways possibly involved in HTS responses in P. palustre, such as plant hormone signal transduction, brassinosteroid biosynthesis, phenylpropanoid biosynthesis, pentose and glucuronate interconversions, diterpenoid biosynthesis, flavonoid biosynthesis, etc. Further weighted gene co-expression network analysis (WGCNA) identified 14 modules and 61 hub genes closely related to the response to HTS in P. palustre. The hub genes included peroxidase 51-like (TRINITY_DN34017_c0_g1), UDP-glucuronate 4-epimerase 1-like (GAE1, TRINITY_DN815_c0_g3), NAC domain-containing protein 1 (NAC, TRINITY_DN328_c0_g1), UGT73A13 (TRINITY_DN8437_c0_g2), universal stress protein 7 (USP7, TRINITY_DN6361_c0_g2), malonyl-coenzyme: anthocyanin 5-O-glucoside-6’’’-O-malonyltransferase-like (5MaT1, TRINITY_DN3589_c0_g1), ent-kaurene synthase 5 (KSL5, TRINITY_DN5126_c0_g1), ABC transporter (TRINITY_DN39495_c0_g1, TRINITY_DN10383_c0_g1), etc. This study investigated the molecular mechanism of heat tolerance in P. palustre at the gene expression level, providing a scientific basis for heat-tolerant breeding of P. palustre.